High-pressure structural and electrical properties of pyrochlore: Enhanced octahedral distortions and electrical resistance of La2Sn2O7 - Shufan Jia; H. Saqib; Daniel Errandonea; Yuxin Hu; Bin Zeng; Xiangyu Chen; Alfonso Munoz; Silvana Radescu; Andres Mujica; Yongsheng Zhao; S. Rahman; Ning Dai (Journal of Materials Research and Technology)
The effect of high pressure on the structural and electrical properties of La2Sn2O7 have been studied using Raman spectroscopy, in situ angle dispersive X-ray diffraction (ADXRD) and alternating current (AC) impedance spectroscopy. High-pressure Raman spectroscopy illustrates the enhanced distortions of SnO6 octahedron with pressure. ADXRD patterns, up to the highest pressure (30.2 GPa) have been refined using the Rietveld method. Furthermore, AC impedance spectroscopy measurements revealed that the resistance of La2Sn2O7 increases continuously with pressure. On the other hand, first-principles calculations were also employed to investigate the electronic properties and structural evolution of pyrochlore La2Sn2O7, providing a theoretical basis for the interpretation of the experimental observation that pyrochlore La2Sn2O7 becomes more insulating under compression. The combined experimental and theoretical results suggest that the cubic phase of La2Sn2O7 remains stable under high pressure. Pyrochlore La2Sn2O7 is an important material due to its potential applications in various fields, including solid oxide fuel cells and nuclear waste immobilization, owing to its structural stability and electronic properties. Understanding its behaviour under high pressure is crucial for optimizing its performance in these applications.